Here's the question you clicked on:
burhan101
use transformations to solve ;
\[\large y=-2f (\frac{ 1 }{ 2 } x) +3\]
can someone explain ?
What I think : \[g(x)=-2f(\frac{ 1 }{ 2 }x) +3\] If you evaluate for x=4, \[g(4)=-2f(2)+3\] by looking at the graph, you see that f(2) = 0 thus, \[g(4)=3\]
I'm not sure what they mean by "use transformations"
they mean like apply all the changes to the graph looking at the formula above like the (-) means it's reflect on the x axis, but i dont understand the rest
You'd have to draw a second graph of \[y_{g}=g(x)\], using the formula and the graph \[y_{f}=(\frac{ 1 }{ 2 }x)\]
\[y _{g}=-2y _{f}+3\] \[y _{f}\] is found by looking at the first graph, at a value on the x-axis that is x/2